Witchcraft and Discourses of Identity and Alterity in Early Modern England, c. 1680-1760 - McMurtry, Charlotte (Université d'Ottawa / University of Ottawa, 2020)
Witchcraft beliefs were a vital element of the social, religious, and political landscapes of England in the late seventeenth and early eighteenth centuries. English society, buffeted by ongoing processes of social, economic, and religious change, was increasingly polarized along material, ideological, and intellectual lines, exacerbated by rising poverty and inequality, political factionalism, religious dissension, and the emergence of Enlightenment philosophical reasoning. The embeddedness of witchcraft and demonism in early modern English cosmologies and quotidian social relations meant that religious and existential anxieties, interpersonal disputes, and threats to local order, settled by customary self-regulatory methods at the local level or prosecuted in court, were often encompassed within the familiar language and popular discourses of witchcraft, social order, and difference. Using trial pamphlets, newspapers, periodicals, and intellectual texts, this thesis examines the imbrications of these discourses and their collectively- determined meanings within the increasingly rationalized legal contexts and widening world of Augustan England, demonstrating the often deeply encoded ways in which early modern English men and women made sense of their own experiences and constituted and re-constituted their identities and affinities. Disorderly by nature, an inversion of natural, religious, and social norms, witchcraft in the Christian intellectual tradition simultaneously threatened and preserved order. Just as light could not exist without dark, or good without evil, there could be no fixed state of order: its existence was determined, in part, by its antithesis. Such diacritical oppositions extended beyond the metaphysical and are legible in contemporary notions of social difference, including attitudes about the common and poorer sorts of people, patriarchal gender and sexual roles, and nascent racial ideologies. These attitudes, roles, and ideologies drew sharp distinctions between normative and transgressive appearances, behaviours, and beliefs. This thesis argues that they provided a blueprint for the discursive construction of identity categories, defined in part by alterity, and that intelligible in witchcraft discourses are these fears of and reactions to disruptive and disorderly difference, otherness, and deviance—reactions which could themselves become deeply disruptive. In exploring the intersections of poverty, gender, sexuality, and race within collective understandings of witchcraft in Augustan England, this thesis aims to contribute to our understandings of the complex and dynamic ways in which English men and women perceived themselves, their communities, and the world around them.
Keywords: History; British History; Early Modern History; Cultural History; Social History; Witchcraft; Popular Culture